The militarization of European space policy - Hörber, Thomas; Oikonomu, Ēraklēs ca. 20./21. Jh (Routledge, Taylor & Francis Group, 2024)
"This book is focused on militarisation as the nucleus of EU space policy and the interrelatedness of European security, industrial competitiveness and military capabilities in the shaping of this policy. The EU and key member-states have increasingly joined the US, China and Russia, among others, in regarding space assets as critical military, but also economic, industrial and technological, enablers. The book tackles this issue by, first, shedding light on the military aspects of EU space policy, with special emphasis on the security and defence dimensions of projects such as Galileo, Copernicus, Space Situational Awareness, and Satellite Communication. In this context, contributors confront the empirical aspect of developments, including the role of different institutional actors and the involvement of specific member-states. Further, the volume analyzes the discursive, ideological, normative and theoretical foundations of the use of space by the EU for strategic purposes, drawing on the broad spectrum of European integration / International Relations theory. Last, but not least, the volume discusses initiatives outside the EU by key global space players, with an emphasis on the US and transatlantic space relations. All chapters maintain a solid empirical foundation, in the form of geographical or issue-related focus, with an area-specific emphasis on the EU as a whole, transatlantic relations, the policies of key member-states (such as France and Italy), and core space powers such as the US, China and India. This book will be of much interest to students of space power, security studies, European politics and International Relations"--
Keywords: Europäische Union; Militärpolitik; Raumfahrtpolitik; Sicherheitspolitik; Militärische Raumfahrt; Space security; European Union countries / Military policy; Astronautics, Military / European Union countries; Security, International / European Union countries; Sécurité spatiale; Pays de l'Union européenne / Politique militaire; Astronautique militaire / Pays de l'Union européenne; Astronautics, Military; Military policy; Security, International; European Union countries